Hubungan Penggunaan dan Lama Penggunaan Jenis Kontrasepsi Hormonal Dengan Kejadian Keputihan Pada Akseptor Keluarga Berencana Di Wilayah Kerja Puskesmas Kartasura Sukoharjo - Sari, Hesti F; , Yuli Kusumawati, SKM., M. Kes (Epid); , Anisa Catur Wijayanti, SKM., M.Epid (2015)
Hormonal contraceptive is one of the most effective method of contraception and reversible to prevent conception. Whitish can be caused because the use of hormonal contraceptive containing in the use of hormonal contraception, the incidence of vaginal discharge increased 50 percent compared with women not wearing a hormonal contraceptives. The purpose of this research is to know the relationship the use of hormonal contraceptives with the the incidence of vaginal discharge on acceptors in the work area of Puskesmas Kartasura, Sukoharjo. The kind of research this is observational research analytic with the approach of cross-sectional. The population in this research was acceptors in the work area of Puskesmas Kartasura many as 6847, and sample many as 97 was done using simple random sampling. Statistical testing technique using test chi square. The research results show that there is a relationship the use of hormonal contraceptives (syringe, pills and implants) with the incidence of vaginal discharge scene (pvalue = 0,012), there was an association long the use of injecting the incidence of vaginal discharge scene (pvalue = 0,000), there was an association long the use of pills with the genesis the incidence of vaginal discharge (pvalue = 0,023), there was no contact long the use of implants with the genesis the incidence of vaginal discharge (pvalue= 0,400 ) on acceptors in the work area of Puskesmas Kartasura, Sukoharjo.